The type and linguistic foci of oral corrective feedback in the L2 classroom: A meta-analysis. (July 2016) - Brown, Dan
Research on corrective feedback (CF), a central focus of second language acquisition (SLA), has increasingly examined how teachers employ CF in second language classrooms. Lyster and Ranta's (1997) seminal study identified six types of CF that teachers use in response to students' errors (recast, explicit correction, elicitation, clarification request, metalinguistic cue, and repetition) as well as target linguistic foci (lexical, phonological, and grammatical errors). These taxonomies have remained dominant in observational studies conducted in a growing range of second language teaching contexts. Several studies have acknowledged that contextual factors may influence how teachers provide CF (e.g. Mori, 2002; Sheen, 2004) with few generalizable conclusions. The present study brings together research in this area in the first comprehensive synthesis of classroom CF research seeking to aggregate proportions of CF types teachers provide, as well as their target linguistic foci. Findings reveal that recasts account for 57% of all CF while prompts comprise 30%, and grammar errors received the greatest proportion of CF (43%). The study further identifies a range of contextual and methodological factors (i.e. moderators) that may influence CF choices across teaching contexts, such as student proficiency, teacher experience, and second/foreign language context. A clearer picture of the patterns of CF that teachers provide and the variables that influence these choices serves to complement the growing body of research investigating the efficacy of CF in second language pedagogy.